Stigma as a barrier and sex work as a protective factor for HIV testing among trans women in Nepal - Erin C. Wilson; Caitlin M. Turner; Manisha Dhakal; Sanjay Sharma; Anuj Rai; Rajesh Lama; Swagata Banik; Sean Arayasirikul (Public Library of Science (PLoS), 2023)
Stigma towards trans women in Nepal creates individual and system-level risks for HIV. A critical protective factor is access to HIV prevention. Research is needed to determine the impact of stigma on HIV testing among trans women in Nepal. We conducted a secondary analysis of data collected using respondent driven sampling in 2019 on HIV risk among trans women in Nepal. Data analysis was restricted to trans women who were HIV negative at testing through the parent study. Descriptive statistics, tests for bivariable associations between HIV testing and stigma variables, and binomial Poisson regression were conducted to examine HIV testing outcomes. There were 173 participants who tested negative for HIV in our sample. The majority were under age 35 (59%) and most had a grade school education or less (64.7%). No trans women were homeless and most rented a room (70.5%) or owned their home (19.7%). The majority were currently sex workers (57.8%). Almost all HIV-negative trans women had ever been tested for HIV (90.8%), but only 53.5% in the last 3 months. The most frequently cited reason for not having been tested was thinking they were at low risk for HIV (40.9%) and being afraid of receiving a positive test result (22.7%). HIV and anti-trans stigma were high across most measures, including that almost all (94.2%) believed that most people in Nepal would discriminate against people with HIV. And most participants thought trans women were not accepted in Nepali Society (65.9%). Most participants also reported high social support (70.5%). Social cohesion among participants varied, with most experiencing medium (41.6%) or high (33.5%) social cohesion. Just over half had high social participation (55.5%). Participants who reported current sex work had lower prevalence of not testing for HIV in the last 3 months (prevalence ratio, PR = 0.54, 95% confidence interval, 95%CI = 0.32-0.92, p = 0.02). Every one-unit increase in social cohesion was associated with 1.05 times the prevalence of not testing for HIV in the last 3 months (95%CI = 1.01-1.09, p-value = 0.02). Trans women who did sex work were more likely to be HIV tested while those who were more socially connected to peers were less likely to have recently been tested for HIV. HIV stigma may result in fear of social rejection from peers if one tests positive. Interventions that focus on addressing stigma within trans women's social networks and strategies to mitigate HIV stigma in society may result in increased frequency of HIV testing among trans women in Nepal.